REFORMULASI TEOLOGI DARI EKSKLUSIF KE INKLUSIF - HAJAM HAJAM (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2018)
Theology, in practical, appears into two poles: first, exclusive based normative theology; second, inclusive based socio-anthropocentric. Both of these exclusive and inclusive ways of thinking can be a paradigm in every belief of school of thoughts (Madzhab) or social groups (mass organizations). These two ways of logical reasoning (exclusive and inclusive) afoot each other, and they frequently do not come together at one point; indeed, both of them are often contradictive and clash each other. Theology constructed for the present context is the one that is completely living among the members of religious community and that may give motivation to act in the reality of human life. Theology is practically hoped to be an ideology that realty functions for practical needs of human, especially for the backward community. Keywords: theology, exclusive, inclusive, divinity, humanity.